Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/su151712771
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Concerns in Social Commerce: The Impact of Gender

Ibrahim Mutambik,
John Lee,
Abdullah Almuqrin
et al.

Abstract: Today, social commerce is one of the most rapidly growing subsectors of e-commerce, creating new opportunities for brands of all types and sizes. However, despite its popularity and potential, social commerce faces significant challenges, including issues of privacy, trust and ethics. This paper sets out to identify key aspects of privacy which influence ongoing user engagement with social commerce, so that social media, and other social commerce, platforms can more effectively address the issue. In particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 97 publications
(153 reference statements)
0
4
0
Order By: Relevance
“…Empirical research has shown that the theory of planned behavior supports a wide range of behaviors (Yang & Xu, 2021). Thus, it is commonly used in information-systems research to predict and analyze different forms of behavior (Mutambik et al, 2023d;Sommestad et al, 2019;Zhang et al, 2020). Communication with others in organizations can affect people's feelings, responses, and behaviors.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Empirical research has shown that the theory of planned behavior supports a wide range of behaviors (Yang & Xu, 2021). Thus, it is commonly used in information-systems research to predict and analyze different forms of behavior (Mutambik et al, 2023d;Sommestad et al, 2019;Zhang et al, 2020). Communication with others in organizations can affect people's feelings, responses, and behaviors.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Attitudes are based on three components: a cognitive component, the ideas and beliefs about something; an affective component, involving how the person, issue, or event affects emotions and feelings; and a behavioral component, determining how attitude can affect behavior or intention to perform a behavior (Cherry, 2018). Moreover, past and present experience shapes attitudes (Ajzen, 2001;Mutambik et al, 2023b;Safa et al, 2017). This applies to IS, where a positive attitude toward policy compliance should result in more employee compliance.…”
Section: Attitudementioning
confidence: 99%
“…Fortes and Rita describe the important role of privacy factors in online transactions [18]. Furthermore, Mutambik explains that privacy-related data is a significant concern requiring protection [19]. Tseng proposes that privacy impacts trust in social commerce application [15], a point reinforced by Fortes and Rita [18].…”
Section: Introductionmentioning
confidence: 99%